JENIS DAN SEBARAN SATWA BURUNG PADA HUTAN PANTAI NEGERI MAMALA KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Randa Cahya Sahmony; John Sahusilawane; Andri Tuhumury (MARSEGU : Jurnal Sains dan Teknologi, 2024)
The purpose of this study was to determine the types and distribution of birds in the coastal forest of Negeri Mamala, Leihitu District, Central Maluku Regency. The method used to determine the types and distribution of birds is the point count method or count points made in five plots. The results of the study showed that there were 14 species of birds at the research location, namely river kingfisher (Todirhamphus chloris), long-tailed shrike (Pycnonotus aurigaster), pariah eagle (Milvus migrans), garden fantail (Riphudara leucophrys), great egret (Ardea alba), honey sriganti (Nectarinia jugularis), metallic black dove (Columba vitiensis), rock dove (Columba livia), Eurasian kingfisher (Alcedo atthis), black magpie (Dicrurus macrocercus), common turtle dove (Streptopelia chinensis), plain swallowtail (Aerodramus vanikorensis), cow swallowtail (Collocalia escuenta), and white-nested swallowtail (Aerodramus fuciphagus). Distribution of birds found on route 1 (5 individuals), route 2 (7 individuals), route 3 (9 individuals), route 4 (12 individuals), route 5 (9 individuals), route 6 (10 individuals), route 7 (11 individuals) with the total frequency of all types of birds per route, namely route 1 (3%), route 2 (2.66%), route 3 (4.33%), route 4 (5.33%), route 5 (4.33%), route 6 (4.67%) and route 7 (5.33%).